Identification of Natural Compounds as Potential COVID-19 Main Protease (Mpro) Inhibitors: A Comprehensive Study and In silico Evidence - Devi, Arti; Dwibedi, Vagish; Jain, Sahil; Kaur, Gursharan; Khan, Zaved Ahmed; Mandal, Sudip Kumar; Shiven, Aditya; Shah, Kamal; Dewangan, Hitesh Kumar; Rath, Santosh Kumar (Current Pharmaceutical Design, 2025)
SARS-CoV-2, the virus responsible for COVID-19, has resulted in a devastating global impact with millions of lives lost. Remdesivir and 2-DG are among the few drugs authorized for emergency use against COVID-19, but concerns about their efficacy and side effects persist. Vaccines have been developed and approved, yet the emergence of viral mutations has raised questions about their effectiveness against new variants. Natural compounds with antiviral properties have shown promise in combating SARS-CoV-2. The review highlights the potential of medicinal plant compounds, particularly in targeting the virus' main protease, a crucial component for viral replication. Natural, plant-derived compounds represent a promising avenue for COVID-19 therapeutics. Further clinical validation is necessary to ascertain their efficacy and safety in treating COVID-19. This underscores the importance of continued research into alternative treatments for combating this global health crisis. This review examines the potential of natural, plant-derived compounds as safe and cost-effective alternatives for combating COVID-19. It summarizes the pathogenesis of SARS-CoV-2 and the ongoing drug studies and identifies natural compounds with known antiviral properties. Additionally, it explores the potential of medicinal plant compounds in targeting the SARS-CoV-2 main protease through in silico and molecular docking studies.
Keywords: SARS-CoV-2